2015
DOI: 10.1159/000431337
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury after Transcatheter Aortic Valve Replacement: A Systematic Review and Meta-Analysis

Abstract: Background: The objective of this meta-analysis was to evaluate the risk of acute kidney injury (AKI) in patients who underwent transcatheter aortic valve replacement (TAVR). Methods: A literature search was performed using MEDLINE, EMBASE, the Cochrane Database of Systematic Reviews and clinicaltrials.gov from inception through October, 2014. Studies that reported relative risks, ORs, or hazard ratios comparing the AKI risk in patients who underwent TAVR versus those who underwent surgical aortic valve replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…We did, however, find a significant decrease in acute renal failure and an increase in rates of pacemaker implantations in the TAVR group as compared to SAVR group. Although the incidence of acute renal failure has been examined in other trials (21)(22)(23)(24), this is the first instance where a large data set has detected a significant benefit of TAVR over SAVR in a non-high risk population. Our data suggests that TAVR may result in improved neurologic outcomes and reduced post-procedure MIs but this study lacked the power to demonstrate a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…We did, however, find a significant decrease in acute renal failure and an increase in rates of pacemaker implantations in the TAVR group as compared to SAVR group. Although the incidence of acute renal failure has been examined in other trials (21)(22)(23)(24), this is the first instance where a large data set has detected a significant benefit of TAVR over SAVR in a non-high risk population. Our data suggests that TAVR may result in improved neurologic outcomes and reduced post-procedure MIs but this study lacked the power to demonstrate a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…90,[92][93][94][96][97][98][99][100] Patients requiring renal replacement therapy (RRT) after TAVR had on average a 3-fold increase in 30-day mortality and a 3.3-fold increase in 1-year mortality as compared with patients with AKI of lower severity. In a recent meta-analysis of randomized controlled trials in TAVR, there was no association between TAVR and reduced risks of short term mortality (<1 year, RR 0.84, 95% CI 0.56-1.26); 102 patients that developed AKI following TAVR stayed 1.5 to 2 fold longer in hospital than patients without AKI. A recent study 120 looked at incidence, causes and predictors of early (<=30 days) and late unplanned hospital re-admissions after TAVR; CKD (p=0.013) was found to be associated with late unplanned re-admission after TAVR.…”
Section: Association Of Aki With Mortality Morbidity and Long-term Rmentioning
confidence: 98%
“…A recent study 120 looked at incidence, causes and predictors of early (<=30 days) and late unplanned hospital re-admissions after TAVR; CKD (p=0.013) was found to be associated with late unplanned re-admission after TAVR. Further to the above, a metaanalysis suggested that 30-day mortality was 7.8%-29% for patients with AKI following TAVR and 5.5%-46% for those with AKI after SAVR, the rates being 2-16 times higher than in patients without AKI after the procedure 102 .…”
Section: Association Of Aki With Mortality Morbidity and Long-term Rmentioning
confidence: 99%
“…Despite increasing evidence of treating intermediate surgical-risk patients (7)(8)(9), many patients elected for TAVR commonly have renal insufficiency (11,12), one of important predictors for acute kidney injury (AKI) development (13). In addition, AKI following TAVR is very prevalent, varying from 15% up to 57% (10,11,(14)(15)(16). Although patients with chronic kidney disease (CKD) carry a higher risk of developing AKI, improvement in estimated glomerular filtration rate (eGFR) following surgical aortic valve replacements (SAVRs) has been demonstrated in patients with CKD after relief of severe aortic valve diseases (17,18).…”
Section: Introductionmentioning
confidence: 99%